Mechanisms of Persistent Neurobiological Changes Following Adolescent Alcohol Exposure: NADIA Consortium Findings. (14th August 2019) - Crews, Fulton T.; Robinson, Donita L.; Chandler, L. Judson; Ehlers, Cindy L.; Mulholland, Patrick J.; Pandey, Subhash C.; Rodd, Zachary A.; Spear, Linda P.; Swartzwelder, H. Scott; Vetreno, Ryan P.
Abstract : The Neurobiology of Adolescent Drinking in Adulthood (NADIA) Consortium has focused on the impact of adolescent binge drinking on brain development, particularly on effects that persist into adulthood. Adolescent binge drinking is common, and while many factors contribute to human brain development and alcohol use during adolescence, animal models are critical for understanding the specific consequences of alcohol exposure during this developmental period and the underlying mechanisms. Using adolescent intermittent ethanol (AIE) exposure models, NADIA investigators identified long‐lasting AIE‐induced changes in adult behavior that are consistent with observations in humans, such as increased alcohol drinking, increased anxiety (particularly social anxiety), increased impulsivity, reduced behavioral flexibility, impaired memory, disrupted sleep, and altered responses to alcohol. These behavioral changes are associated with multiple molecular, cellular, and physiological alterations in the brain that persist long after AIE exposure. At the molecular level, AIE results in long‐lasting changes in neuroimmune/trophic factor balance and epigenetic–microRNA (miRNA) signaling across glia and neurons. At the cellular level, AIE history is associated in adulthood with reduced expression of cholinergic, serotonergic, and dopaminergic neuron markers, attenuated cortical thickness, decreased neurogenesis, and altered dendritic spine and glial morphology. This constellation of molecular and cellular adaptations to AIE likely contributes to observed alterations in neurophysiology, measured by synaptic physiology, EEG patterns, and functional connectivity. Many of these AIE‐induced brain changes replicate findings seen in postmortem brains of humans with alcohol use disorder (AUD). NADIA researchers are now elucidating mechanisms of these adaptations. Emerging data demonstrate that exercise, antiinflammatory drugs, anticholinesterases, histone deacetylase inhibitors, and other pharmacological compounds are able to prevent (administered during AIE) and/or reverse (given after AIE) AIE‐induced pathology in adulthood. These studies support hypotheses that adolescent binge drinking increases risk of adult hazardous drinking and influences brain development, and may provide insight into novel therapeutic targets for AIE‐induced neuropathology and AUDs.